Emowars: Interactive Game Input Menggunakan Ekspresi Wajah - Andry Chowanda (ComTech: Computer, Mathematics and Engineering Applications, 2013)
Research in the affective game has received attention from the research communities over this lustrum. As a crucial aspect of a game, emotions play an important role in user experience as well as to emphasize the user’s emotions state on game design. This will improve the user’s interactivity while they playing the game. This research aims to discuss and analyze whether emotions can replace traditional user game inputs (keyboard, mouse, and others). The methodology used in this research is divided into two main phases: game design and facial expression recognition. The results of this research indicate that users preferred to use a traditional input such as mouse. Moreover, user’s interactivities with game are still slightly low. However, this is a great opportunity for researchers in affective game with a more interactive game play as well as rich and complex story. Hopefully this will improve the user affective state and emotions in game. The results of this research imply that happy emotion obtains 78% of detection, meanwhile the anger emotion has the lowest detection of 44.4%. Moreover, users prefer mouse and FER (face expression recognition) as the best input for this game.